Do the cations in clay and the polymer matrix affect quantum dot fluorescent properties?. (14th December 2015) - Wei, Wenjun; Liu, Cui; Liu, Jiyan; Liu, Xueqing; Zou, Linling; Cai, Shaojun; Shi, Hong; Cao, Yuan‐Cheng
Abstract: This paper studied the effects of cations and polymer matrix on the fluorescent properties of quantum dots (QDs). The results indicated that temperature has a greater impact on fluorescence intensity than clay cations (mainly K + and Na + ). Combined fluorescence lifetime and steady‐state spectrometer tests showed that QD lifetimes all decreased when the cation concentration was increased, but the quantum yields were steady at various cation concentrations of 0, 0.05, 0.5 and 1 M. Poly(ethylene oxide) (PEO), poly(vinyl alcohol) (PVA) and diepoxy resin were used to study the effects of polymers on QD lifetime and quantum yield. The results showed that the lifetime for QDs 550 nm in PEO and PVA was 17.33 and 17.12 ns, respectively; for the epoxy resin, the lifetime was 0.74 ns, a sharp decrease from 24.47 ns. The quantum yield for QDs 550 nm changed from 34.22% to 7.45% and 7.81% in PEO and PVA, respectively; for the epoxy resin the quantum yield was 2.25%. QDs 580 nm and 620 nm showed the same results as QDs 550 nm. This study provides useful information on the design, synthesis and application of QDs–polymer luminescent materials. Copyright © 2015 John Wiley & Sons, Ltd.